Combining streptozotocin and unilateral nephrectomy is an effective method for inducing experimental diabetic nephropathy in the ‘resistant’ C57Bl/6J mouse strain - Uil, Melissa; Scantlebery, Angelique M. L.; Butter, Loes M.; Larsen, Per W. B.; de Boer, Onno J.; Leemans, Jaklien C.; Florquin, Sandrine; Roelofs, Joris J. T. H. (Scientific reports, 2018)
Diabetic nephropathy (DN) is the leading cause of chronic kidney disease. Animal models are essential tools for designing new strategies to prevent DN. C57Bl/6 (B6) mice are widely used for transgenic mouse models, but are relatively resistant to DN. This study aims to identify the most effective method to induce DN in a type 1 (T1D) and a type 2 diabetes (T2D) model in B6 mice. For T1D-induced DN, mice were fed a control diet, and randomised to streptozotocin (STZ) alone, STZ+unilateral nephrectomy (UNx), or vehicle/sham. For T2D-induced DN, mice were fed a western (high fat) diet, and randomised to either STZ alone, STZ+UNx, UNx alone, or vehicle/sham. Mice subjected to a control diet with STZ +UNx developed albuminuria, glomerular lesions, thickening of the glomerular basement membrane, and tubular injury. Mice on control diet and STZ developed only mild renal lesions. Furthermore, kidneys from mice on a western diet were hardly affected by diabetes, UNx or the combination. We conclude that STZ combined with UNx is the most effective model to induce T1D-induced DN in B6 mice. In our hands, combining western diet and STZ treatment with or without UNx did not result in a T2D-induced DN model in B6 mice.